Elicitation of Bacoside Content Using Plant Growth Regulators in Cell Suspension Culture of Bacopa monnieri (L.) Wettst. (Plant Tissue Culture and Biotechnology, 2018)
Cell suspension culture is used for the optimization of plant growth regulators used for the elicitation of bacoside content of Bacopa monnieri (L.) Wettst. Callus induction was carried out on MS supplemented with 2, 4-D (0.5 mg/l) by using leaf explants. For suspension culture MS liquid medium was supplemented with constant α-naphthalene acetic acid (0.5 mg/l) and casein hydrolysate (1 g/l) as well as the varied concentrations of 6-benzyleadenine, kinetin, thidiazuaron and chitosan. It was observed that bacoside production was increased by 6- benzyleadenine (0.5 mg/l), Kn (0.5 mg/l) and thidiazuaron (0.25 mg/l) was 3.07, 3.79 and 3.97 mg/g, respectively. This indicates that lower concentration of growth regulator favor the bacoside enhancement under in vitro conditions, while chitosan affects the bacoside production in suspension culture. In this study thidiazuaron at 0.25 mg/l induces maximum elicitation of bacoside content i.e. 3.97 mg/g.Plant Tissue Cult. & Biotech. 28(2): 191-199, 2018 (December)